Problematika Pasal 5 dan Pasal 6 Undang-Undang Ketenagakerjaan terhadap Rekrutmen Berbasis Gaya Hidup - Ardhani Ahimsha Maulidan; Mega Dewi Ambarwati (Media Hukum Indonesia (MHI), 2026)
Articles 5 and 6 of Law Number 13 of 2003 on Manpower guarantee equal opportunities to obtain employment and equal treatment without discrimination. Nevertheless, recruitment practices continue to impose requirements relating to applicants' lifestyle status, including smoking habits, tattoos, and other personal characteristics that are not necessarily relevant to the performance of the job. This raises concerns regarding the adequacy of these provisions as a normative basis for distinguishing between lawful recruitment requirements and discriminatory ones. This normative legal research employs statutory, conceptual, and analytical approaches, drawing upon legislation, legal literature, and scholarly journals as its legal sources. The findings indicate that Articles 5 and 6 do not provide sufficient legal parameters for assessing the validity of recruitment requirements based on applicants' lifestyle status. Accordingly, such assessments should be guided by the principles of relevance and proportionality to ensure the effective protection of the principle of non-discrimination.